A Decade of South Africa’s Acoustic Tracking Array Platform: An Example of a Successful Ocean Stewardship Programme - Murray, Taryn S.; Elston, Chantel; Parkinson, Matthew C.; Filmalter, John D.; Cowley, Paul D. (Frontiers in Marine Science, 2022)
The Blue Economy is a global initiative aimed at using marine resources to create economic viability and environmental sustainability. While successes have been reported, for example, in Europe and China, examples of African successes are notably missing. Abject poverty, unemployment and food insecurity are everyday concerns on the African continent; however, its large latitudinal coverage gives rise to extremely biodiverse marine fauna, which could promote socio-economic development of coastal communities through initiatives such as sustainably-managed fisheries. In order to improve sustainability via improved management, information on a species and its habitat is needed, particularly how it moves and in which areas it occurs. Acoustic telemetry is a powerful tool used to determine the movements of aquatic animals, the success of which has led to the development of several large-scale networks throughout the globe, including South Africa’s Acoustic Tracking Array Platform. This network, formally in place for the last decade, has now matured, and data are revealing insights into residency, habitat connectivity and transboundary movements of a multitude of animals, with some species having been continually detected for the past 10 years. These data are also actively being incorporated into marine spatial planning efforts, with the aim of protecting threatened and endemic species. Due to knowledge generation, successful benefit-sharing arrangements, and dedication to engage with the public and other stakeholder groups, the ATAP represents a highly successful example of ocean stewardship in Africa.